(untitled) (Homiletic, 2022)
In this article, I study preachers’ practice of preaching to children. Using Theodore Schatzki’s concept of "timespace," I analyse how four timespaces – school, age-appropriation, "ordinary" preaching, and the Bible – are configured in the practice of preaching to children. I also explore what normative assumptions preachers have concerning preaching to children and how these contribute to the configuration of the practice. Finally, I discuss why the timespace of age-appropriation seems to dominate every negotiation in preachers’ practice of preaching to children, and I suggest that recent homiletical research makes essential contributions that preachers engaging in preaching for children should consider.